Work plan for the Sustainable development working group (SDWG) 2001-2002. - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2001)
Arctic Council working group Sustainable Development Working Group (SDWG)'s work plan for the years 2001-2002, approved by SAOs at the Arctic Council's Senior Arctic Officials meeting in Rovaniemi, Finland, June 12-13, 2001.